Znaczenie literatury i jej dydaktyki w procesie akwizycji języka obcego = Importance of literature and its didactics in the process of foreign language acquisition - Kozłowski, Aleksander (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article presents the aims, functions and importance of literary texts in the process of foreign language acquisition. The main aim of using this kind of texts on foreign language lesson is the necessity of permanent extension and studying the knowledge of new vocabulary. Literature can fulfil in this process the following functions:
Keywords: literatura; dydaktyka literatury; języki obce